2019
DOI: 10.1002/jgf2.267
|View full text |Cite
|
Sign up to set email alerts
|

Myxedema coma accompanied by sick sinus syndrome and hypoventilation: A case report

Abstract: Myxedema coma is an emergency presentation of hypothyroidism, and cardiopulmonary manifestations of the disease are related to a high mortality rate. We herein report a case of myxedema coma accompanied by sick sinus syndrome requiring temporary cardiac pacing and hypercapnic respiratory failure in an 87‐year‐old woman. This case is unique because both of the cardiac and pulmonary manifestations were reversible and successfully treated with thyroid hormone replacement. Our case indicates that early detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…We present a case of myxedema coma refractory to traditional treatments. Fatality from myxedema coma is frequently due to a delayed diagnosis, but the condition responds very well to intravenous levothyroxine if initiated early and aggressively [1,2]. However, in our patient the diagnosis was recognized immediately, but strangely remained refractory to treatment for a prolonged period of time.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We present a case of myxedema coma refractory to traditional treatments. Fatality from myxedema coma is frequently due to a delayed diagnosis, but the condition responds very well to intravenous levothyroxine if initiated early and aggressively [1,2]. However, in our patient the diagnosis was recognized immediately, but strangely remained refractory to treatment for a prolonged period of time.…”
Section: Discussionmentioning
confidence: 55%
“…Fatalities of myxedema coma are caused by severe hypotension, hypoventilation, deterioration of mental status, and renal complications [1]. Even these complications do respond to intravenous thyroid replacement if initiated early [2]. If the diagnosis is recognized early and treated aggressively, and if the patient does not die from the lethal complications while awaiting treatment, then the thyroid function tests rapidly improve within about five days [3].…”
Section: Introductionmentioning
confidence: 99%
“…1 The mechanisms of T3 5 Hypothyroidism is known to be related with several ECG abnormalities including sinus bradycardia, prolonged QT interval, low voltage, prolonged the action potential duration of cardiomyocytes and heart block at varying degrees. 2 Cardiac K+ and L-type Ca++ channels in patients with hypothyroidism are affected by serum T3 and as a result, ventricular repolarization anomalies develop, which is one of the reasons why hypothyroidism patients have been reported to have an increased risk of ventricular arrhythmias. 7 Several studies have also confirmed that QT dispersion increases in dominant and subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…To cite an example, Harada et al reported a case of hypothyroidism that caused SSS requiring temporary cardiac pacing, which was reversible and was successfully treated with levothyroxine without a need for a permanent pacemaker. 2 Some scholars have reported an 87-year-old patient who developed highgrade atrioventricular block, which was successfully Figure 4 The changes in clinical course and levothyroxine dose, as well as laboratory data including free T3 (FT3), free T4 (FT4), and thyroid-stimulating hormone (TSH) were shown. From day1 to day 3, we kept giving the patient a dose of 25 ug of levothyroxine per day, and then gradually increased to100ug daily from the 14th day, while this patient's temporary cardiac pacing was discontinued on day 17, which might indicate that thyroxine supplementation may have improved the electrocardiogram abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few studies have described patients with myxedema coma presenting with bradyarrhythmia's, who were successfully treated with thyroid hormone replacement only, without the need for permanent pacemaker implantation. Harada et al reported a case of a myxedema coma in an elderly female pa-tient who presented with sick sinus syndrome and type two respiratory failure, which was successfully managed with thyroid hormone replacement (Harada et al, 2019). Also, Waseem et al (2018) reported a case of an elderly male with a history of undertreated hypothyroidism who presented with atrial fibrillation with a slow ventricular response as well as a high degree atrioventricular block.…”
Section: Discussionmentioning
confidence: 99%